Histoenzymic Distribution Pattern in Liver of Sheep During Prenatal and postnatal Development - Choudhury, A. R.; Singh, Opinder (Indian Journal of Veterinary Anatomy, 2016)
The study was conducted on liver of sheep fetuses (n=9) ranging from 43–122 days of gestation (3.7-30.7 cm crown anus length) and three samples from sheep below one year of age to study histoenzymic distribution of different enzymes. The study revealed most of the enzymes of prenatal liver showed weak to moderate activity in vascular areas and moderate to intense in hepatocytes. The intensity of enzymic activity increased with the advancement of age of fetuses. Since the hemopoietic activity took place during early prenatal life, the hemopoietic areas were weekly reactive. The enzyme activity was correlated with development, differentiation and maturation of different histological components. In postnatal liver the reaction remained moderate to intense in vascular areas and mostly intense reaction in hepatocytes and perivascular areas.